Lattice strain suppresses point defect formation in halide perovskites - YAVUZ, İLHAN (My University, 2022)
We computationally investigate the impact of crystal strain on the formation of native point defects likely to be formed in halide perovskites; A-site cation antisite (I-A), Pb antisite (I-Pb), A-site cation vacany (V-A), I vacancy (V-I), Pb vacancy (V-Pb), and I interstitial (1). We systematically identify compressive and tensile strain to CsPbI3, FAPbI(3), and MAPbI(3) perovskite structures. We observe that while each type of defect has a unique behaviour, overall, the defect formation in FAPbI(3) is much more sensitive to the strain. The compressive strain can enhance the formation energy of neutral I-pb and I-I up to 15% for FAPbI(3), depending on the growth conditions. We show that the strain not only controls the formation of defects but also their transition levels in the band gap: A deep level can be transformed into a shallow level by the strain. We anticipate that tailoring the lattice strain can be used as a defect passivation mechanism for future studies.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Yüzeyler ve arayüzeyler; İnce filmler ve nanosistemler; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Surfaces, Interfaces, Thin Films and Nanosystems; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; KİMYA, FİZİKSEL; Temel Bilimler (SCI); NANOBİLİM VE NANOTEKNOLOJİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); FİZİK, UYGULAMALI; CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); NANOSCIENCE & NANOTECHNOLOGY; PHYSICS; MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); PHYSICS, APPLIED; Surfaces and Interfaces; Metals and Alloys; Materials Chemistry; Statistical and Nonlinear Physics; Chemistry (miscellaneous); General Materials Science; General Chemistry; Physical and Theoretical Chemistry; Surfaces, Coatings and Films; Physical Sciences; perovskite solar cells; halide perovskites; defect formation; lattice strain; TOTAL-ENERGY CALCULATIONS; TOLERANCE FACTOR; SOLAR-CELLS; SEMICONDUCTORS; FORMAMIDINIUM; PERFORMANCE; EFFICIENCY; STABILITY; DYNAMICS; CATIONS